Macropinosomes as units of signal transduction - Swanson, Joel A.; Yoshida, Sei (Philosophical transactions of the Royal Society of London. Series B. Biological sciences, 2019)
Macropinosome formation occurs as a localized sequence of biochemical activities and associated morphological changes, which may be considered a form of signal transduction leading to the construction of an organelle. Macropinocytosis may also convey information about the availability of extracellular nutrients to intracellular regulators of metabolism. Consistent with this idea, activation of the metabolic regulator mechanistic target of rapamycin complex-1 (mTORC1) in response to acute stimulation by growth factors and extracellular amino acids requires internalization of amino acids by macropinocytosis. This suggests that macropinocytosis is necessary for mTORC1-dependent growth of metazoan cells, both as a route for delivery of amino acids to sensors associated with lysosomes and as a platform for growth factor-dependent signalling to mTORC1 via phosphatidylinositol 3-kinase (PI3K) and the Akt pathway. Because the biochemical signals required for the construction of macropinosomes are also required for cell growth, and inhibition of macropinocytosis inhibits growth factor signalling to mTORC1, we propose that signalling by growth factor receptors is organized into stochastic, structure-dependent cascades of chemical reactions that both build a macropinosome and stimulate mTORC1. More generally, as discrete units of signal transduction, macropinosomes may be subject to feedback regulation by metabolism and cell dimensions. This article is part of the Theo Murphy meeting issue ‘Macropinocytosis’.